Answer :

Put x = sin2θ


And we know sin2θ +cos2θ = 1


By putting these in above equation, we get


= sin–1


= sin–1


= sin–1


= sin–1


= sin–1(sin θ)


= θ


But θ = sin–1x


The given equation simplification to sin–1x.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers